2021
DOI: 10.1038/s41422-021-00582-x
|View full text |Cite
|
Sign up to set email alerts
|

An App knock-in rat model for Alzheimer’s disease exhibiting Aβ and tau pathologies, neuronal death and cognitive impairments

Abstract: A major obstacle in Alzheimer’s disease (AD) research is the lack of predictive and translatable animal models that reflect disease progression and drug efficacy. Transgenic mice overexpressing amyloid precursor protein (App) gene manifest non-physiological and ectopic expression of APP and its fragments in the brain, which is not observed in AD patients. The App knock-in mice circumvented some of these problems, but they do not exhibit tau pathology and neuronal death. We have generated a rat model, with thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
52
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 117 publications
(177 reference statements)
1
52
0
Order By: Relevance
“…Importantly, the initial characterizations of the TgF344-AD rat model by Cohen and colleagues found no observable sex differences on the tasks assessed, and consequently, a majority of the subsequent studies on this model combined male and female rats 5 . This may account for some of the discordant behavioral findings, as previous AD rodent models have displayed sex differences in cognitive function and neuropathology 14 , 15 , and from a clinical perspective, it is well established that females are at a greater risk of developing AD compared to males 16 . Overall, using different paradigms to assess specific memory domains, combining sexes and ages, as well as a lack of statistical power to detect nuanced memory changes, likely contribute to the lack of accordance in behavioral findings.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, the initial characterizations of the TgF344-AD rat model by Cohen and colleagues found no observable sex differences on the tasks assessed, and consequently, a majority of the subsequent studies on this model combined male and female rats 5 . This may account for some of the discordant behavioral findings, as previous AD rodent models have displayed sex differences in cognitive function and neuropathology 14 , 15 , and from a clinical perspective, it is well established that females are at a greater risk of developing AD compared to males 16 . Overall, using different paradigms to assess specific memory domains, combining sexes and ages, as well as a lack of statistical power to detect nuanced memory changes, likely contribute to the lack of accordance in behavioral findings.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the mouse hippocampal neuron cell line HT22 was used as a cell model, while the Aβ-induced cells were used to construct a cell model of AD. Studies have shown that Aβ caused the changes in apoptosis-related phenotypes [ 32 ]. After the treatment, the apoptosis rate of cells was significantly increased, while the expression of anti-apoptotic protein Bcl-2 was decreased and the expression of pro-apoptotic protein Bax was increased (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…3 ). In rats with amyloid precursor protein knock-in, mAb005 immunoreactivity precedes MC-1 immunoreactivity by ∼10 months ( 74 ). While MC-1 antibody is thought to recognize misfolding events occurring between pretangle formation and tangle deposition ( 75 ), mAb005 appears to recognize even earlier misfolding/oligomerization events that generate what we termed esoTau.…”
Section: Discussionmentioning
confidence: 99%